Social Status and Livelihood Strategies in Rural Area: A Case Study of Sinurjoda VDC, Dhanusha - Paudyal, Narayan Prasad (The Third Pole: Journal of Geography Education, 2018)
Sustainable livelihood is an integrated and holistic concept particularly for addressing poverty. This paper highlights the copping livelihood strategies in Sinurjoda Village Development Committee of Dhanusha district basing the social status of local people. The study is based on primary and secondary sources of data. Qualitative and quantitative methods have been used to analyze the information. The findings of the study apparently revel that due to illiteracy, high family size, deep rooted blind belief on religion and local language, people in the study area do not hold good status in the VDC as compared to the national scenario. Agriculture and livestock farming have been paramount activities of the local people. About 62.30 percent people are involved in this profession. Remittance holds second position in this respect. People seem to be eager to fly abroad specially to gulf countries for employment including India. The study also depicts that this VDC has some (8.93%) squatters who are spending very miserable lives as compared to the people having own land. The Third Pole: Journal of Geography Vol. 17: 83-98, 2017